Digital-Worksheets Based Creative Problem Solving to Support Students Mathematical Thinking for Audio-Visual Students - Susanti, Ely; Wulandari, Trisna; Hapizah; Indaryanti; Isrok’atun; Simarmata, Ruth Helen (Mathematics Education Journal, 2025)
Mathematical thinking involves how individuals present, understand, and critically examine mathematical truths, considering how their relation to representation or imagination. However, students often exhibit low mathematical thinking skills. Previous research shows that digital worksheets based on creative problem-solving can foster these skills, yet the relationship between mathematical thinking and learning styles remains unexplored. This study aims to develop innovative digital worksheets based on creative problem solving, categorized as valid, practical, and effective in enhancing students' mathematical thinking with audio-visual learning styles. The study employs a development method comprising two main stages: a preliminary study (analysis and design) and a formative study (evaluation and revision). Data collection instruments include tests, observations, validation sheets, questionnaires, and interviews. The analysis integrates both quantitative and qualitative approaches. The study involved 15 audio-visual learners from 24 eighth-grade students at SMP Srijaya Negara Palembang. The results indicate that students excel in specializing and identifying problems based on given information. Their generalizing skills, including finding patterns and relationships are strong. However, their conjecturing and convincing skills require improvement, particularly in making connections and reasoning. The digital worksheets were deemed 93% valid and practical, significantly enhancing students' mathematical thinking, particularly for those with an audio-visual learning style. While students demonstrated excellent skills in specialization and good skills in generalization, there is still a need for improvement in conjecturing and convincing due to errors in mathematical reasoning.